MP10: Does early intervention improve outcomes for patients with acute ureteral colic?. (May 2019) - Innes, G.; McRae, A.; Grafstein, E.; Andruchow, J.; Law, M.; Scheuermeyer, F.
Abstract : Introduction : The optimal initial management approach for ureteral colic is unclear. Guidelines recommend spontaneous passage for most patients, but early stone intervention may rapidly terminate acute episodes. We compared 60-day treatment failure rates in matched patients undergoing early intervention versus spontaneous passage.Methods : We used administrative data and structured chart review to study all emergency department (ED) patients at nine Canadian hospitals who had an index ureteral colic visit and a computed tomography (CT) confirmed 2.0-9.9 mm stone during 2014. Using Cox Proportional Hazards models, we assessed 60-day treatment failure, defined as hospitalization or rescue intervention, in patients undergoing early intervention compared to propensity-score matched controls undergoing trial of spontaneous passage.Results : From 3, 081 eligible patients, mean age 51 years and 70% male, we matched 577 patients in each group (total 1154). Control and intervention cohorts were balanced on all parameters and propensity scores, which reflect the conditional probability a patient would undergo early intervention, were similarly distributed. In the time to event analysis, 21.8% in both groups experienced the composite primary outcome of treatment failure (difference = 0%; 95% CI, -4.8 to 4.8%). Early intervention patients required more ED revisits (36.1% v. 25.5%; difference 10.6%; 95% CI 5.3 to 15.9%) and more 60-day hospitalizations (20.1% v. 12.8%). The strongest predictors of adverse outcome were stone size, proximal or middle stone location, and ED length of stay.Conclusion : If applied broadly to patients with 2.0-9.9mm ureteral stones, an early interventional approach was associated with similar rates of treatment failure, but more hospitalizations and emergency revisits. Research clarifying subgroups most likely to benefit will facilitate better targeting of early intervention, potentially reducing patient morbidity and improving system utilization.